Pengembangan soal matematika model PISA menggunakan konteks rumah adat lamban dalom - Alghofari, Wildan; Ikashaum, Fertilia (Program Studi Pendidikan Matematika, Universitas Nusantara PGRI Kediri, 2024)
The PISA 2022 results show that Indonesian students' mathematical literacy scores have decreased again. One of the reasons is that students need more practice working on PISA model questions. This study aims to develop PISA model math problems using the context of Lamban Dalom traditional houses that are valid, practical, and have potential effects. This research used the Design Research method of development study type. The research stages include Preliminary and Formative Evaluation stages (expert review, one-to-one, small group, field test). The research results are a set of mathematical problems of the PISA model of space and shape content with the context of Lampung Lamban Dalom, which is valid in terms of content, construct, and language, practical, and has a potential effect of 5 items. It is applicable based on small group trials and potentially impacts the field test stage. In addition, students also become more challenged to solve similar problems even though the scores obtained still need to meet the criteria for completeness. Future researchers are advised to develop PISA model math problems with different content and contexts further by involving more potential users and conducting trials with more students.